A Rare Case Report of Bilateral Traumatic Carotid Cavernous Fistula - Rafika Sari Fadli; M Sidik; Syntia Nusanti (Majalah Oftalmologi Indonesia, 2020)
Objective : To increase the awareness for ophthalmologist in diagnosing rare case of bilateral traumatic carotid cavernous fistula that could lead to serious complications. Case description : A 44 years old woman came with chief complaint of squint and diplopia since one month after traffic accident. She had been underwent orbital bone fracture repair at previous hospital immediately. There was complaint of headache, blurred vision, double vision and pain on the eyes one month after trauma. There was no history of redness or proptosis. Examination revealed 6/6 for the right and 6/8.5 for the left eye corrected visual acuity, 30 degrees exotropia, normal intraocular pressures (IOP), restriction on eyes movement especially on the left eye, normal anterior and posterior segment, and no bruit. CT orbital revealed bilateral dilated and tortuous of the ophthalmica vein with suspicious of carotid cavernous fistula (CCF). Patient developed slowly progressive conditions such as proptosis non axial on the left eye, redness with corkscrew appearance on both eyes, restriction of the ocular movement and also founded bruit on both eyes within two months follow up. CT angiography revealed CCF bilateral type A. Patient underwent digital subtraction angiography (DSA) and balloon embolization four months after diagnosed. Conclusion : Although bilateral carotid cavernous fistula is a rare case, performing a suitable diagnostic examination would help to prevent devastating outcome. Prognosis depends on severity and time span from symptoms to treatment.